The determinants of income inequality in OECD countries [2008-2017] / Nuradilah Muzammir - Muzammir, Nuradilah (2022)
There are many researchers studying about the determinants of income inequality. However, there are many different results that indicate from each researcher and have various of factors that effects on income inequality. This study is using a panel data to explore the determinants of income inequality using the variables such as economic growth, foreign direct investment, government final consumption expenditure, economic freedom and democracy. This research using the latest data of income inequality from Standardized World Income Inequality Database (SWIID) and focusing on 29 of OECD countries within 10 years of period from 2008 until 2017. The findings indicate the results that foreign direct investment and economic freedom have positive effect towards income inequality. However, the findings shows the negative effects of economic growth, government final consumption expenditure and democracy on income inequality. this may become a sensitive issue but the gap of income of individuals between the richest and poorer have to be reduce.